Swimbladder properties of Cyclothone spp. in the northeast Atlantic Ocean and the Western Mediterranean Sea - Sarmiento-Lezcano, Airam N.; Olivar, M. Pilar; Caballero, María José; Couret, María; Hernández-León, Santiago; Castellón, Arturo; Peña, Marian (Frontiers in Marine Science, 2023)
Non-migratory bristlemouth fishes (Cyclothone spp.) are the most abundant vertebrates on Earth and play an important role in the biological carbon pump by remineralizing the organic carbon at deep ecosystems. Acoustic data and net sampling are often used in combination to estimate fish and zooplankton biomass, but it may be subject to several sources of errors when applied to mesopelagic species: the allocation of echoes to species for instance has often been biased by not considering Cyclothone spp. due to the use of nets targeting larger fishes. Furthermore, the acoustic properties of the target organisms must be well understood in order to convert acoustic density into numerical density. This study provides information on the acoustic properties of six Cyclothone species inhabiting the meso- and bathypelagic layers in the North Atlantic Ocean and Mediterranean Sea, including swimbladder location within the body, fat tissue content, morphology, morphometry, and fish body-mass density. The studied species showed an irregularly-shaped functional physoclistous swimbladder, with well-developed gas gland and rete mirabile and numerous capillaries in C. braueri and C. pseudopallida (from 400 to 600 m), and a fat-invested swimbladder in species with deeper vertical distribution (C. livida, C. microdon, C. pallida and C. pygmaea). The fat content increased with depth and latitude, reducing the swimbladder space that could contain gas. Changes in swimbladder size and volume during growth were analyzed for the shallower species, where swimbladder volume and equivalent radius followed a negative allometric growth in relation to body length. Finally, values of body-mass density and gas content required for neutral buoyancy were estimated for C. braueri and C. pygmaea collected between 350 and 550 m and for C. pallida and C. pseudopallida sampled in the 450-700 m layer. Results in this study highlight the change in scattering behavior of Cyclothone species from gas-bearing organisms in the upper mesopelagic zone to the fluid-like scattering of the deeper and northern individuals. The different parameters provided will help to better estimate their target strength although further work is needed, particularly for the case of individuals with partially invested swimbladders with an irregular fat-free shape.